Occurrence of the Colistin Resistance Gene mcr-1 and Additional Antibiotic Resistance Genes in ESBL/AmpC-Producing Escherichia coli from Poultry in Lebanon: A Nationwide Survey - Myriam Mikhayel; Sébastien O. Leclercq; Dolla Karam Sarkis; Benoît Doublet (Microbiology Spectrum, 2021)
ABSTRACT The objective of the present study was to determine genomic characteristics of expanded-spectrum cephalosporin (ESC)-resistant Escherichia coli spreading in healthy broilers in Lebanon in 2018. Rectal swabs (n = 280) from 56 farms were screened for the presence of ESC-resistant E. coli isolates. Antimicrobial susceptibility and extended-spectrum β-lactamase (ESBL)/AmpC production were determined by the disk diffusion method. Whole-genome sequencing (WGS) of 102 representative isolates of E. coli was performed to determine their phylogenetic diversity, serotypes, sequence types (ST), acquired resistance genes, and virulence-associated genes. Fifty-two out of 56 farms housed broilers carrying ESC-resistant E. coli isolates. These farms had large and recurrent antimicrobial practices, using, for some of them, critically important antibiotics for prophylactic and therapeutic purposes. Among the 102 sequenced multidrug-resistant (MDR) E. coli isolates, the proportion of ESBL, plasmid-mediated AmpC β-lactamase (pAmpC) producers, and ESBL/pAmpC coproducers was 60%, 27.6%, and 12.4%, respectively. The most prevalent ESBL/pAmpC genes were blaCMY-2, blaCTX-M-3, blaCTX-M-15, blaCTX-M-27, and blaCTX-M-14b (n = 42, n = 31, n =15, n = 9, and n = 7, respectively). These ESBL/pAmpC producers were distributed in different STs, most being well-known avian-associated and sometimes pathogenic STs (ST-10, ST-48, ST-93, ST-115, ST-117, and ST-457). Phylogenetic single nucleotide polymorphism (SNP) analysis confirmed their genetic diversity and wide dispersion across the Lebanese territory. Most isolates were also resistant to ciprofloxacin (101/102 with 3 QRDR mutations), and 19/102 isolates from 11 unrelated STs also carried the mobile resistance gene mcr-1. This survey illustrates the alarming prevalence of MDR E. coli resistant to medically important antibiotics in broilers in Lebanon. This advocates the need for surveillance programs of antimicrobial resistance in Lebanon and the reduction of excessive use of antibiotics to limit the spread of MDR E. coli in food-producing animals. IMPORTANCE Poultry production is a main contributor of the global trend of antimicrobial resistance arising from food-producing animals worldwide. In Lebanon, inappropriate use of antibiotics is frequent in chickens for prophylactic reasons and to improve productivity, resulting in an alarming prevalence of extended-spectrum β-lactamase (ESBL)/AmpC-producing Escherichia coli, also resistant to other medically important antibiotics (i.e., colistin and ciprofloxacin). Their complex genomic epidemiology highlighted by an important genetic diversity suggests that these resistance determinants are largely spreading in enteric bacteria in Lebanese poultry. Further molecular surveillance is needed to understand the country-specific epidemiology of ESBL/AmpC and mcr-1 genes in Lebanese poultry production. In addition, decisive interventions are urgently needed in order to ban the use of critically important antibiotics for human medicine in food-producing animals and limit the spread of antibiotic resistance in Lebanon.